2012
DOI: 10.1007/s00018-012-1143-x
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-linked determinants of zygotic genome activation

Abstract: The merging of the maternal and paternal genomes into a single pronucleus after fertilization is accompanied by a remarkable reconfiguration of chromatin in the newly formed zygote. The first stages of embryonic chromatin remodeling take place in the absence of ongoing transcription, during a species-specific developmental time-frame. Once post-fertilization chromatin states are organized, zygotic genome activation (ZGA) is initiated, and embryonic transcripts gradually take control of development. We review h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 98 publications
0
21
0
Order By: Relevance
“…The methylation status of H3K4 affects gene regulation in developing embryos (Gao et al, ; Ostrup et al, ). We observed more H3K4me and H3K4me2 in early‐ compared to late‐cleaving embryos during the EGA period, which implies that greater modification early in cleavage correlates with a higher probability of reaching the blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methylation status of H3K4 affects gene regulation in developing embryos (Gao et al, ; Ostrup et al, ). We observed more H3K4me and H3K4me2 in early‐ compared to late‐cleaving embryos during the EGA period, which implies that greater modification early in cleavage correlates with a higher probability of reaching the blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%
“…A critical milestone of development is the maternal‐to‐zygote transition, the period when the embryo genome is activated (Wong et al, ; Lee et al, ); failure to undergo proper embryonic genome activation (EGA) leads to developmental arrest. Several epigenetic modifications and changes in chromatin structure occur during the EGA period (Ostrup et al, ; Lee et al, )—all of which are needed to regulate gene expression in developing embryos (Mason et al, ; Beaujean, , b; Cheedipudi et al, ). Removal of repressive marks and addition of activation marks, such as methylation of lysine 4 in histone 3 (H3K4me3), are among the epigenetic changes observed during EGA (Gao et al, ; Ostrup et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the relationship between zygotic transcription and chromatin regulation has been uncertain. Chromatin regulation could precede and initiate zygotic transcription (Meier et al, 2018;Østrup et al, 2013). Conversely, zygotic transcription may help shape chromatin structure, a model that has been tested by several studies: A study that analyzed the spatial genome organization in fly embryos revealed that early expressed genes correlate with the boundaries of Topologically Associating Domains (TADs).…”
Section: Zygotic Transcription and Chromatin Organizationmentioning
confidence: 99%
“…During the first cell cycles of the zebrafish embryos, some histone marks such as H3K4 (H3: H3 family of histones; K: standard abbreviation for lysine; 4: position of amino acid residue counting from the N-terminus), H3K9 or H3K27 were acquired for epigenetic reprogramming [203,231]. Cayuso et al reviewed the roles of chromatin modifications in zebrafish development and regeneration [232].…”
Section: Epigenetic Effects Of Ionizing Radiation In Zebrafishmentioning
confidence: 99%